FORMULASI DAN UJI AKTIVITAS DEODORANT STICK EKSTRAK ETANOL DAUN SIRIH MERAH (Piper ornantum N.E.BR ) TERHADAP BAKTERI staphylococcus epidermidis - Fitri, Nurul; Rani, Zulmai; Lubis, Minda Sari; Nasution, Haris Munandar (FARMASAINKES: JURNAL FARMASI, SAINS, dan KESEHATAN, 2025)
Red betel leaf (Piper ornatum N.E.Br) is one of several plants that have antibacterial properties so that it can be selected as an active ingredient in deodorants because of its effectiveness as an antibacterial. Red betel leaf contains secondary metabolites, namely alkaloids, flavonoids, tannins and essential oils. The purpose of this study was to determine the formulation of ethanol extract of red betel leaf (Piper ornatum N.E.Br) made in the form of a deodorant stick preparation with good characteristics and to determine the concentration of the deodorant stick preparation in inhibiting Staphylococcus epidermidis bacteria. The study was conducted experimentally including the manufacture of extracts by the maceration method. In this study, ethanol extract of red betel leaf with concentration variations of 1, 2 and 3%. The preparation was tested for organoleptic, homogeneity, pH, melting time, melting point, and antibacterial activity. The content of the phytochemical screening results of the ethanol extract of red betel leaf showed that there were flavonoids, alkaloids, tannins, saponins, and triterpenoids so that they have the potential to inhibit bacteria. The resulting deodorant stick meets the requirements of pH test, melting time test, melting point test and has bacterial inhibitory activity. At a concentration of 1% it is categorized as moderate with an inhibition zone of 6-10 while for a concentration of 2% and 3% it is categorized as strong with an inhibition zone of 10-20 mm.